A legal study of adulterated traditional medicines and health supplements in Malaysia / Siti Ainul Fadhilah Jamaludin - Jamaludin, Siti Ainul Fadhilah (2018)
Malaysia is not exempted from the global issue of adulterated traditional medicines and health supplements. Adulteration by illegal addition of undeclared poison is a major concern since it impose a very high risk to the public health. Various efforts and strategies have been taken by Pharmacy Enforcement Division in enforcing the laws in controlling the sale and supply of adulterated traditional medicines and health supplements. However abundance of such products in market chain showed that the efforts are still insufficient to curtail the problem. Thus in the absence of comprehensive literature of legal study in controlling the sale and supply of adulterated traditional medicines and health supplements in Malaysia, this study fill the gap via qualitative research where analysis of provisions of laws and interviews were conducted. This study suggests possible solutions to overcome the challenges faced by pharmacy enforcement in performing duties in entry point, raids, laboratory testing, advertisement control, and prosecution. Accordingly, some recommendation for instance, provisions review, enhancement in empowerment officer, tighter control in entry points, punitive action to the advertiser as well as increase of public education towards the risk of consumption of these fraudulent products are suggested in this study.